Optimization of Guidance and Counseling via Social Media by Bhabinkamtibmas in Preventing the Crime of Theft in the Lamongan Police Jurisdiction - Marpaung, Marta Christina (Advances in Police Science Research Journal, 2024)
This study is based on the fact that there are increasing numbers of cases of motor vehicle theft (Curanmor) which occurred in the jurisdiction of the Lamongan Police. Prevention efforts are crucial solve this problem. One approach taken is through guidance and counseling by Bhabinkamtibmas to the public via social media as a preemptive action from the National Police. This research aims to investigate and identify how to optimize guidance and outreach via social media by Bhabinkamtibmas can influence the level of prevention the crime of theft in the jurisdiction of the Lamongan Police. The research method used is a qualitative approach with the type of writing field research. This research uses primary and secondary data sources which were explored using using data collection techniques through interviews, observations, and document studies. Theory used are management theory, SWOT theory, and communication theory with concepts optimization, guidance and counseling concept, Bhabinkamtibmas concept, prevention concept, and Curanmor concept. The research results found that guidance and counseling activities were carried out through social media which was analyzed using Perkap Number 7 of 2021 and Perkap Number 21 of 2007 is not yet optimal. There are internal and external factors that influence it both from the relevant Bhabinkamtibmas limited ability to create innovative social security messages on social media and online people in the region. Based on the discussion of the research results, guidance and counseling is carried out through social media by Bhabinkamtibmas in preventing criminal acts of theft from being carried out optimally. The author provides constructive suggestions including optimizing media use social by Bhabinkamtibmas to convey the message of preventing theft by pay attention to supporting and inhibiting factors.